2022
DOI: 10.3390/ijerph19010602
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Disorders and Selected Risk Factors of Ventilator-Associated Pneumonia (VAP) in Patients Treated in the Intensive Care Ward—A Retrospective Study

Abstract: Introduction: The development of pneumonia in patients treated in intensive care wards is influenced by numerous factors resulting from the primary health condition and co-morbidities. The aim of this study is the determination of the correlation between nutritional status disorders and selected risk factors (type of injury, epidemiological factors, mortality risk, inflammation parameters, age, and gender) and the time of pneumonia occurrence in patients mechanically ventilated in intensive care wards. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Invasive surgery for older patients and those with cerebrovascular disease may lead to prolonged intubation, even at our institution. In these cases, tracheostomy and aggressive nutritional management may reduce the occurrence of VAP (21,22). We would also like to consider tracheostomy for longterm management in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive surgery for older patients and those with cerebrovascular disease may lead to prolonged intubation, even at our institution. In these cases, tracheostomy and aggressive nutritional management may reduce the occurrence of VAP (21,22). We would also like to consider tracheostomy for longterm management in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Any further responses from the reviewers can be found at the end of the article lung disease, chronic renal failure, and thyroid disorders. 22,23 Mechanical ventilation, 24 especially if prolonged for more than two weeks, 21 reintubation or tracheostomy, 25 major chest or abdominal surgery, 26 as well as previous antibiotic exposure, especially to broad-spectrum antibiotics, 27 are possible risk factors for VAP. Of note, some studies have reported an increased incidence of HAP when the gastric pH is increased with the use of medications including H 2 receptor blockers, antacids, or proton pump inhibitors.…”
Section: Revised Amendments From Versionmentioning
confidence: 99%
“…Common risk factors for VAP may include sex, Acute Physiology and Chronic Health Evaluation (APACHE) II score, hypoproteinemia, state of consciousness, prior antibiotic therapy, age, intubation times, mechanical ventilation days, tracheotomy, and underlying diseases such as diabetes and chronic obstructive pulmonary disease [7][8][9][10][11]. Furthermore, previous studies have shown that oral care, bed elevation of 30-45 • , and continuing aspiration of subglottic secretions might decrease VAP risk [12][13][14].…”
Section: Introductionmentioning
confidence: 99%